Tracer Study Alumni Program Studi Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Raden Fatah Palembang - Setyaningsih, Kris (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2021)
This study aims to determine the profile of alumni from the Islamic Education Management Study Program at the Faculty of Tarbiyah and Teacher Training, Raden Fatah State Islamic University in Palembang, focusing on their employment status and the alignment of alumni competencies. This research adopts a descriptive research approach with data collection conducted through surveys. The subjects of this study are alumni from the Islamic Education Management Study Program at the Faculty of Tarbiyah and Teacher Training, Raden Fatah State Islamic University in Palembang, who graduated between 2017 and 2019, totaling 30 individuals. The research instrument utilizes a questionnaire consisting of closed and open-ended questions. Data collection is carried out by contacting the alumni, distributing the questionnaires directly and online via Google Forms. The analysis is conducted descriptively using percentage tables. The first job types of the alumni among 30 respondents are as follows: 15 respondents (50%) work in the field of education, 5 respondents (17%) are entrepreneurs, and 10 respondents (33%) work in office administration. The time taken to obtain the first job shows varied responses: less than 1 month for 3 respondents (10%), 1-3 months for 14 respondents (47%), 3-6 months for 8 respondents (26%), more than 6 months for 2 respondents (7%), and more than 1 year for 3 respondents (10%). The first salary amount is distributed as follows: less than Rp 1,000,000 for 9 respondents (30%), between Rp 1,000,000 - Rp 1,500,000 for 6 respondents (20%), between Rp 1,500,000 - Rp 3,000,000 for 10 respondents (33%), and between Rp 3,000,000 - Rp 5,000,000 for 5 respondents (17%). Regarding the alignment of alumni competencies with their first job compared to their expectations during their studies: 3 respondents (10%) felt their competencies were very suitable, 10 respondents (33%) felt they were suitable, 10 respondents (10%) felt they were somewhat suitable, and 3 respondents (10%) felt they were not suitable.